Sensitivity and resistance to apoptosis in the APO-1 (Fas/CD95) system - Debatin, Klaus-Michael (Onkologie, 1996)
The selective induction of apoptosis or programmed cell death in tumor cells represents a new approach in tumor therapy. In lymphoid cells, apoptosis may follow withdrawal of crucial growth factors (death by default). Alternatively, apoptosis may be induced via cell surface molecules such as APO-1 (Fas/ CD95), a 48-kD member of the TNF/NGF- receptor superfami-ly. APO-1 is weakly expressed on resting mature T cells and on the majority of immature thymocytes, and strongly expressed on activated T cells. Triggering of APO-1 by the monoclonal antibody anti-APO-1 on its natural ligand induces apoptosis in most APO-1-positive cell lines. However, in activated T cells, sensitivity to apoptosis is not fixed and depends on the state of activation. In T cell leukemias, a distinct pattern of sensitivity is also found. Mature T cell leukemias e.g. adult T cell leukemia cells (ATL) are sensitive to anti-APO-1-induced apoptosis. In contrast, the majority of APO-1 T-ALL cells representing more immature T cell phenotypes is apoptosis resistant. This resistance is independent of the expression of the antiapoptotic protooncogene bcl-2 and is turned into sensitivity by inhibition of protein synthesis. Thus, resistance towards induction of apoptosis is actively maintained by cellular programs and can be modulated. The identification of cellular factors which determine sensitivity and resistance towards apoptosis may provide new rational approaches in tumor therapy.